Jute Plant- A Bio-Degradable Material in Making Sanitary Pad for Sustainable Development - Agbaku, Comfort Afi; Yahaya, Alimatu Sadia; Junhua, Feng; Chengqi, Shi; Linda, Wangkung (International Journal of Scientific Research and Management (IJSRM), 2020)
This Purpose: Achieving Environmental Sustainability by increasing access to affordable, bio-degradable, and healthy sanitary napkins, the paper aims to shed light on the use of the Jute Plant in place of the chlorine-bleached wood pulp or cotton and packaging.Design/Methodology/Approach: The research is developed based on results drawn from a survey on women (both workers and student) and secondary data collected from researches, papers written on female hygiene, Sustainable development goals, and Research Institute on Jute Plant.Findings: The jute plant can be used to replace the non-biodegradable materials used in making sanitary napkins and that many women are ready to change their napkins for many cost-effective and biodegradable ones.Value: Creating a platform for women to have access to affordable sanitary napkins and conserve the environment. Contributing to sustainable development by positioning the environment in its original state after use.